Robust electrocatalysts from metal doped W18O49 nanofibers for hydrogen evolution. Issue 31 (3rd April 2017) - Zhao, Yuanyuan; Tang, Qunwei; Yang, Peizhi; He, Benlin
Abstract : Electrocatalysts from metal doped W18 O49 nanofibers are robust, high-efficiency and stable for hydrogen evolution. Abstract : We report here robust electrocatalysts from metal doped W18 O49 nanofibers (NFs) for high-efficiency hydrogen evolution. By tuning Pd dosages, the optimal 5 at% Pd doped W18 O49 NFs yield an onset overpotential of only 65 mV and exchange current densities up to 2.36 × 10 −3 mA cm −2 . Moreover, the resultant electrocatalyst is relatively stable during persistent operation.